Sasi Dalam Menunjang Sustainable Ekonomi Masyarakat Adat Saparua - Matitaputty, Jenny Koce (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2021)
This study aims to reveal information about Sasi, which has the principle of sustainability and balance of the relationship between humans and nature, as well as humans and their creators, of course, in line with sustainable living. This research is unique because it explicitly supports a sustainable community economy. An in-depth study using qualitative research is needed to determine how Sasi supports the economic sustainability of the Saparua people. Interviews and observations are the methods used to collect data. After that, an interactive analysis was carried out. The results show that sasi can be implemented to manage quality and economically valuable biological and vegetable natural resources products. Sasi helps every proponent of the economy. For example, the selling price of natural resources of sasi is more profitable because the harvest is abundant in quantity and has a higher selling value because of its quality.